2023
DOI: 10.3390/nu15143220
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Inhibits Exhaustive Exercise-Induced Liver Injury and Transcriptome-Based Mechanism Analysis

Abstract: Exhaustive exercise (EE) induces liver injury and has recently gained much attention. Sulforaphane (SFN) can protect the liver from inflammation and oxidative stress. However, the effects of SFN on EE-induced liver injury and its underlying mechanisms are still unclear. C57BL/6J mice swimming to exhaustion for seven days were used to simulate the liver injury caused by EE. Different doses of SFN (10, 30, 90 mg/kg body weight) were gavage-fed one week before and during the exercise. SFN intervention significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Further, SFN contributed effectively in a muscular dystrophy x-linked (mdx) knock-out model; oral administration of SFN (2 mg/kg/day) for eight weeks, followed by an acute exercise protocol, protected dystrophic muscles from oxidative damage in mdx mice and improved the muscle function, ROS level, and inflammation and reduced immune cell infiltration [40]. Yang et al conducted a study and reported that SFN protected the liver from exhaustive exerciseinduced excessive ROS production [41]. We also reported that a single dose of SFN ad-ministration may protect the liver from exhaustive exercise-induced oxidative stress and inflammation [35].…”
Section: Experimental Studies With Sfn Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, SFN contributed effectively in a muscular dystrophy x-linked (mdx) knock-out model; oral administration of SFN (2 mg/kg/day) for eight weeks, followed by an acute exercise protocol, protected dystrophic muscles from oxidative damage in mdx mice and improved the muscle function, ROS level, and inflammation and reduced immune cell infiltration [40]. Yang et al conducted a study and reported that SFN protected the liver from exhaustive exerciseinduced excessive ROS production [41]. We also reported that a single dose of SFN ad-ministration may protect the liver from exhaustive exercise-induced oxidative stress and inflammation [35].…”
Section: Experimental Studies With Sfn Interventionmentioning
confidence: 99%
“…At the same time, SFN increases the transcriptional activation of these essential genes' expression by restoring the Keap1/Nrf2/ARE pathway [38]. Besides improving endurance capacity, SFN preintervention protects from exhaustive exercise-induced liver damage [41]. Yang et al conducted an animal study with a mild and high dose of SFN and executed exhaustive exercise for seven consecutive days along with SFN treatment and reported that an SFN intervention improved the adequacy of antioxidative stress and reduced inflammation in the liver and therefore diminished liver damage and ameliorated exercise endurance [41].…”
Section: The Activation Of Nrf2 Transcription Factormentioning
confidence: 99%